2008
DOI: 10.1186/1757-1146-1-11
|View full text |Cite
|
Sign up to set email alerts
|

Acral lentiginous melanoma of the foot and ankle: A case series and review of the literature

Abstract: Background: Acral lentiginous melanoma (ALM) is an uncommon, cutaneous malignant tumour which may arise on the foot. Its relative rarity, atypical appearance and late presentation frequently serve as poor prognostic indicators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 55 publications
2
57
1
3
Order By: Relevance
“…Our findings concur with previous publications which have evaluated ALM patients in according to ethnicity (Caucasians and other ethnic groups, such as blacks, Hispanics, and Asians) in the same studies [1, 2, 4, 5, 8] and in separate studies [3, 6, 7]. In 17 population-based cancer registries, with a total number of 1,413 American subjects with histologically confirmed cases of ALM, the proportion of ALM among all melanoma subtypes was greatest in nonwhites, accounting for 36% of all melanomas in blacks, 18% in Asian/Pacific Islanders, 9% in Hispanic whites, and only 1% in non-Hispanic whites [1].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings concur with previous publications which have evaluated ALM patients in according to ethnicity (Caucasians and other ethnic groups, such as blacks, Hispanics, and Asians) in the same studies [1, 2, 4, 5, 8] and in separate studies [3, 6, 7]. In 17 population-based cancer registries, with a total number of 1,413 American subjects with histologically confirmed cases of ALM, the proportion of ALM among all melanoma subtypes was greatest in nonwhites, accounting for 36% of all melanomas in blacks, 18% in Asian/Pacific Islanders, 9% in Hispanic whites, and only 1% in non-Hispanic whites [1].…”
Section: Discussionsupporting
confidence: 93%
“…Most (78.3%) ALM were found on the lower limbs and they were thicker than overall melanomas, i.e., in contrast to only 41.3% of ALM, 70% of overall melanomas were diagnosed at a thickness of less than 1 mm. In a retrospective review on 27 patients with miscellaneous ethnic groups from a tertiary skin tumor center, the majority of the patients were white ( n = 16; 59.3%) and female (74%), with an average age of 62.7 years, who primarily suffered from ALM around or below their ankles, and most of the lesions emerged on the plantar surfaces (62%) [2]. The mean depth of the lesions for females and males was 3.68 and 4.41 mm, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the results of other groups. [14,16,17] For example, Fortin et al [14] found an initial misdiagnosis rate of 25%, while Bristow and Acland [16] reported a rate of incorrect diagnosis of 33%. Thus, melanomas of the feet seem to be more frequently misdiagnosed as compared to melanomas from other body sites where the overall misdiagnosis rate is approximately 10%.…”
Section: Discussionmentioning
confidence: 99%
“…The palms and plantar foot are also the most common sites of ALM reported in Asia, although typical percentages range from 44% [16] to 69% [13], rather than 100% of ALM diagnosed at CSC. Known duration of lesion prior to presentation in other studies of ALM ranges from 13.5 months [17], to 27 months [16], where this case series had a 18.3 months average.…”
Section: Discussionmentioning
confidence: 96%